Analisis Kepuasan Pelanggan IndiHome berdasarkan Kualitas Pelayanan, Harga, dan Promosi - Chalvin Septianarditya; Moechammad Nasir (Jurusan Akuntansi Politeknik Negeri Pontianak, 2022)
The goal to be achieved by doing this research is to analyze the influence of service quality, price and promotion on customer satisfaction. The results of this study are expected to be a guide for leaders in determining service quality, price and promotion of customer satisfaction. This type of research is survey research with a quantitative research approach and uses primary data. The population in this study were 100 customers. The sample used was 100 respondents with the sampling technique in this study using non probability sampling technique with saturated sample type for data collection. Based on the results of this study, it can be concluded that: 1) The quality of service has a significant positive effect on the satisfaction of IndiHome customers. 2) Price has a positive significant effect on IndiHome customer satisfaction. 3) Promotion positively affect IndiHome customer satisfaction.